PREVENTIONAL SCREENING: ALL PROS AND CONTRAS - N. V. Pogosova; Yu. M. Yufereva; I. V. Samorodskaya; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2016)
Recently, medical community and mass media actively discuss the need for broad screening programs, criteria of those, investigation methods, frequency of start-up, etc. The article focuses on the main screening programs for adult citizens ofGreat Britain,USA,Australia,JapanandRussia.